A study in the development of curriculum for primary teacher education in Nepal - Pradhananga, Gajendra Bahadur 1936- (s.n.], 1971)
This study presented a description on how curriculum development was carried out for the primary teacher education in Nepal,how far it is suitable, realistic, and practical in the country and its needs, and how far it corresponds with contemporary development in the teacher education concepts, content, and methods abroad. The study made an analysis of the factors involved in the development of primary teacher education curriculum. It made use of the present National Education Plan; reports, observations, and studies made on the primary teacher education program and its curriculum in Nepal in particular, as well as reports, periodicals and books on curriculum for teacher education in Asian region in general.